Analysis Of The Influence Of Tax Officer Services, Sanctions For Tax Negligence And Awareness Of Paying Tax On Taxpayer Compliance - Manap, Abdul; Mustangin; Rini Yulia Sasmiyati; Norman Edy; Zainuddin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study aims to ascertain the effects of tax officer services, tax knowledge, tax payer awareness, and tax penalties on taxpayer compliance. Causal study research is the research methodology employed. A questionnaire was used in this study's data collection process. The study's population consists of taxpayers who own real estate and/or structures in their own names that are used as homes or places of business. Convenience sampling is a non-probability sampling method used in this study. With the use of the SPSS software, a multiple linear regression model was used to examine this research. The study's findings indicate that a number of variables, including taxpayer awareness, tax knowledge, tax penalties, and tax officer services, positively and significantly affect taxpayer compliance. A strong understanding of taxes helps taxpayers comprehend the meaning and intent of the law, which improves compliance. Acknowledging the significance of taxes for the nation's economic progress is a crucial element in enhancing taxpayer compliance. In addition, the presence of imposed tax penalties influences taxpayer compliance, albeit respondents are generally unbiased about this issue. Good service from tax officers also makes a positive contribution to taxpayer compliance because it helps taxpayers fulfill their tax obligations more easily and comfortably.